Organ trafficking: an emerging dimension of illegal trafficking in Nigeria and sub- saharan Africa (2022)
In the last decade, organ trafficking has become one of the ‘booming’ illegal businesses in Nigeria. An array of transnational syndicate is reportedly, responsible for the traffic of illegally harvested human organ across sub-Saharan Africa to the coast of Asia, with India and China identified as top destinations. In 2020, there were reports on popular markets for clandestine sale of human organs in cosmopolitan cities such as Lagos, in Nigeria where, human organs are sold for sums ranging between $ 2,000 US Dollars to $ 3000 US Dollars. There are alleged reports of organ harvesting and export via human trafficking. With increasing reports on the spate of banditry, kidnappings, general insecurity and missing persons in Nigeria, it is imperative to examine this dimension of criminality and the possible legal solutions. While Nigeria has legislation against human trafficking such as the Trafficking in Persons Law Enforcement and Administration Act 2015 and a specialised agency for human trafficking National Agency for the Prohibition of Trafficking in Persons (NAPTIP), Nigeria is only waking up to the sad reality of this dimension of illegal trafficking and has no specific legislation in place to tackle it. This paper examines the legal framework on human trafficking in Nigeria against this backdrop. It adopts a doctrinal and desktop legal research approach in analysing the existing laws on human trafficking and the emerging dimensions of organ trafficking. It considers Nigeria’s legal obligations against the emerging dimensions of illicit organ trade. It proposes a more proactive approach to the subject of organ trafficking in addressing organ trafficking in Nigeria.